Histological Analysis of Breast Muscle Growth in Young Hybrid Chickens in Response to Different Dietary Energy-Protein Ratios - Saragih , Hendry T.S.G.; Harilafindri, N.U.; Perdamaian, A.B.I.; Utomo, R.T.; Puspita, U.E.; Lesmana, I.; Daryono, B.S.; Erwanto, Y. (International Journal of Poultry Science, 2019)
Objective: The aim of this study was to analyze the increase in body weight and growth of breast muscle in hybrid chickens in response to varied dietary energy-protein ratios. Materials and Methods: Four different starter diet formulae were given to one-day-old hybrid chickens (DOCs) for 14 days. One hundred twenty one-day-old hybrid chickens were randomly allotted into four diet groups with 3 replicate pens consisting of 10 DOCs each. The first group was given starter diet I containing 25.1% crude protein (CP) and 3500 kcal kg–1 metabolizable energy (ME), the second group was given starter diet II (22% CP; 3200 ME), the third group was given starter diet III (22.7% CP; 3400 ME) and the fourth group was fed starter diet IV (18% CP; 3200 ME) during a 14-day observation period. Body weight was assessed in chickens post hatching and at 3, 7 and 14 days of age. Muscle weight and size and the cross-sectional area of the myofibers were assessed at 7 and 14 days of age. Results: Body weight, muscle weight and area and myofiber area of the hybrid chickens fed starter diets III and IV were significantly lower than those of chickens fed diets I and II. Conclusion: A hybrid chicken starter diet with an ME-CP ratio of approximately 139-145 is optimal for maximizing body weight and breast muscle growth.